The Bad Wife Handbook - Zucker, Rachel (Book collections on Project MUSE., 2007)
Rachel Zucker's third book of poems is a darkly comic collection that looks unsparingly at the difficulties and compromises of married life. Formally innovative and blazingly direct, The Bad Wife Handbook cross-examines marriage, motherhood, monogamy, and writing itself. Rachel Zucker's upending of grammatical and syntactic expectations lends these poems an urgent richness and aesthetic complexity that mirrors the puzzles of real life. Candid, subversive, and genuinely moving, The Bad Wife Handbook is an important portrait of contemporary marriage and the writing life, of emotional connection and disconnection, of togetherness and aloneness.